Rugby League in Australia between 2001 and 2012: an Analysis of Home Advantage and Salary Cap Violations - Thomas Longden; Greg Kannard (Fondazione Eni Enrico Mattei (FEEM), 2014)
Within this paper, we review whether incidences of salary cap circumvention within the Australian professional rugby league competition led to improved home team wins during the period between 2001 and 2012. In doing so, we show that while the salary cap breach amounts can be attributed to an improved home team win record in the case of the Melbourne Storm, success during the period can also be attributed with other factors such as the management of the club, talent identification and the quality of the coach and/or captain. This raises an important issue surrounding the effectiveness of a salary cap to create a level playing field when uncertainty over the quality and performance of players exists. A notable role of the salary cap violations was the retention of a core group of players that were instrumental in the success that occurred in the 2007 season. As part of the analysis we also review home team advantage. A focus on the NRL is justified due to the peculiar nature of having multiple stadium types within the same city and team. For the year 2012 we find that a match at a traditional Sydney stadium against a non-Sydney team had the highest probability of a home team win when the two teams have had a similar level of success during the season.
Keywords: J31; D39; C23; 330; Salary Cap; Home Advantage; Rugby League